1995
DOI: 10.1093/clinids/21.3.678
|View full text |Cite
|
Sign up to set email alerts
|

Veillonella Myositis in an Immunocompromised Patient

Abstract: Infectious myositis is rather uncommon. When caused by anaerobic organisms, myositis is usually polymicrobial. Trauma, ischemia, or a contiguous focus of infection is often an antecedent of myositis. We report a case of monomicrobial veillonella myositis in an immunocompromised patient. The infection responded to debridement and therapy with metronidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…The genus Veillonella currently consists of eight species (10,16). Veillonella species are rare causes of serious infections such as meningitis, osteomyelitis, prosthetic joint infection, pleuropulmonary infection, endocarditis, and bacteremia (1,2,3,4,12,15,20). In most clinical reports of Veillonella infection, the isolates have not been identified to species level.…”
mentioning
confidence: 99%
“…The genus Veillonella currently consists of eight species (10,16). Veillonella species are rare causes of serious infections such as meningitis, osteomyelitis, prosthetic joint infection, pleuropulmonary infection, endocarditis, and bacteremia (1,2,3,4,12,15,20). In most clinical reports of Veillonella infection, the isolates have not been identified to species level.…”
mentioning
confidence: 99%
“…Little has been written about the occurrence of Veillonella in infections, and it is difficult to evaluate the prevalence and clinical importance of Veillonella species, which are rare causes for serious infections such as meningitis, osteomyelitis, prosthetic joint infection, pleuropulmonary infection, endocarditis, and bacteremia. 10,11,12,13,14,15,16,17,18,19,20 We performed a MEDLINE search using the keywords "Veillonella infection", "anaerobic osteomyelitis", "anaerobic epidural abscess", and "anaerobic spine infection" to search for reports/studies on spine infection caused by Veillonella species, and found only seven cases (Table 1). 11,12,13,14,15,16,17 Including the present case, the median age of the patients infected was 57.8 years (range: 27e76 years).…”
Section: Discussionmentioning
confidence: 99%
“…ont été décrites sur des terrains particuliers : immunodépression [1], toxicomanie intraveineuse [2], prématurité [3,4]. Les atteintes osseuses à Veillonella sont encore plus rares dans la littérature : un cas de sacro-iléite [9], deux cas d'ostéomyélite du rachis [10,11] et un cas de spondylodiscite [12].…”
Section: Discussionunclassified
“…L'ostéomalacie hypophosphatémique oncogénique dite aussi ostéomalacie tumorale (OT) est une entité clinicobiologique rare associant les symptômes d'une ostéomalacie, une hypophosphatémie, un taux normal ou bas non adapté de 1-25 (OH) 2 vitamine D et une tumeur mésenchymateuse habituellement bénigne [1,2]. La résection de la tumeur s'accompagne d'une régression de l'ostéomalacie et d'une normalisation des perturbations biologiques.…”
Section: Discussionunclassified
See 1 more Smart Citation